Evaluasi User Experience Pada Social Application Mobile HAGO Menggunakan Metode Enhanced Cognitive Walkthrough - Tri Andre Mahadika Putra; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
HAGO is a miniature social game app made up of various fun and challenging types of games. Since its launch at the playstore on March 23, 2018, few months have become the number one on the